2016
DOI: 10.1007/s11103-016-0496-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of rice genes preferentially expressed in pollen at an early developmental stage

Abstract: Microspore production using endogenous developmental programs has not been well studied. The main limitation is the difficulty in identifying genes preferentially expressed in pollen grains at early stages. To overcome this limitation, we collected transcriptome data from anthers and microspore/pollen and performed meta-expression analysis. Subsequently, we identified 410 genes showing preferential expression patterns in early developing pollen samples of both japonica and indica cultivars. The expression patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 94 publications
0
16
0
Order By: Relevance
“…In addition, these 793 DEGs in mof1a were further compared with 2987 meiosis-related genes ( Table S10 ), which are specifically or preferentially expressed in PMCs, or were identified from defective meiosis process [ 10 , 26 , 27 , 32 , 33 , 34 , 35 , 40 , 41 ]. A total of 335 DEGs were meiosis-related genes (mDEGs), including 23 down- and 312 up-regulated mDEGs ( Table S11 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these 793 DEGs in mof1a were further compared with 2987 meiosis-related genes ( Table S10 ), which are specifically or preferentially expressed in PMCs, or were identified from defective meiosis process [ 10 , 26 , 27 , 32 , 33 , 34 , 35 , 40 , 41 ]. A total of 335 DEGs were meiosis-related genes (mDEGs), including 23 down- and 312 up-regulated mDEGs ( Table S11 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 335 DEGs were meiosis-related genes (mDEGs), including 23 down- and 312 up-regulated mDEGs ( Table S11 ). Among these 335 mDEGs, 29 mDEGs were differentially expressed in neo-tetraploid line H1 relative to low pollen fertility line LF, 50 mDEGs were differentially expressed in another neo-tetraploid line HF relative to LF, 146 mDEGs were specifically or preferentially expressed in PMCs [ 33 , 34 , 41 ], and 287 mDEGs were differentially expressed in meiotic anthers of autotetraploid lines with low fertility relative to corresponding diploid lines [ 4 , 10 ]. Moreover, nine mDEGs were up-regulated in low pollen fertility lines among three groups (HF/LF, H1/LF, and mof1a /H1), while all of them were differentially expressed in meiotic anthers between different ploidy lines (02428-4x/02428-2x or Taichung65-4x/Taichung65-2x) [ 4 , 10 ], including LOC_Os03g61150 , LOC_Os03g59880 , LOC_Os08g28820 (S-phase kinase association protein 1, Skp1, family member), LOC_Os01g04409 , LOC_Os08g27220 , LOC_Os02g50690 , LOC_Os07g35370 , LOC_Os01g13610 , and LOC_Os11g47809 ( OsMT1a , a type 1 metallothionein) ( Table S12 ).…”
Section: Resultsmentioning
confidence: 99%
“…As we have described for previous investigations, we identified meaningful biological processes and visualized significant metabolic pathways through GO enrichment and MapMan analyses 26 , 63 . Results from the former suggested that biological processes mainly related to carbohydrate metabolism are important in the crosstalk between the drought up-regulation and diurnal rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…To meet the need of efficient wheat genetic engineering and avoid various types of unpredictable expression driven by homologous promoters from other species, more tissuespecific native promoters should be isolated and studied in wheat. Tissue/organ-specific genes and promoters can be commonly screened by microarray and next-generation sequencing (NGS) technology with high efficiency (Endo et al 2004, Ye et al 2012, Nguyen et al 2016. For instance, the organ-specific genes and promoters in seven tissues were efficiently isolated in rice by using microarrays (Chae et al 2016).…”
Section: mentioning
confidence: 99%